2018
DOI: 10.1002/term.2701
|View full text |Cite
|
Sign up to set email alerts
|

Fibre-based scaffolding techniques for tendon tissue engineering

Abstract: Tendon refers to a band of tough, regularly arranged, and connective tissue connecting muscle and bone, transferring strength from muscle to bone, and enabling articular stability and movement. The limitations of natural tendon grafts motivate the scaffold-based tissue engineering (TE) approaches, which aim to build patient-specific biological substitutes that can repair the damaged or diseased tissues. Advances in engineering and knowledge of chemistry and biology have brought forth numerous fibre-based techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 154 publications
(273 reference statements)
2
70
0
Order By: Relevance
“…Collagen is responsible for maintaining the structural integrity and mechanical function of tissues in most multicellular organisms. [28,29] Young's modulus and ultimate tensile stress of TSs in Group 1 at week 6 were in the same order of magnitude as those in native human cartilage (1-15 and 7-13 MPa, respectively). [30,31] Cells in Group 1 were fully differentiated in 2D culture prior to forming TSs; however, cells in Group 2 were differentiated while the cells were compacted into strands.…”
Section: Discussionmentioning
confidence: 65%
“…Collagen is responsible for maintaining the structural integrity and mechanical function of tissues in most multicellular organisms. [28,29] Young's modulus and ultimate tensile stress of TSs in Group 1 at week 6 were in the same order of magnitude as those in native human cartilage (1-15 and 7-13 MPa, respectively). [30,31] Cells in Group 1 were fully differentiated in 2D culture prior to forming TSs; however, cells in Group 2 were differentiated while the cells were compacted into strands.…”
Section: Discussionmentioning
confidence: 65%
“…Native tendon tissue possesses the hierarchical architecture at various scale-levels, consisting of intensively packed aligned collagen fibrils (50-500 nm in diameter), which in turn organize to collagen fibers, and further form a higher level of collagen fascicles (150-1000 μm in diameter) [57,58], as shown in Fig. S2.…”
Section: Discussionmentioning
confidence: 99%
“…Since the tendons are comprised of mechanically strong and regularly arranged connective tissue bands, there has been a continuing effort to develop treatment technologies based on ELSP of tissue engineering scaffolds that can provide for structural and mechanical properties which are similar to the original tendons [3][4][5]. Despite ELSP's ability to provide for ENs with controlled architectures, there remain a number of challenges for tissue engineering, such as cell adherence, growth, and differentiation [2,30].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the developed biomaterials, highly aligned electrospun nanofibrous scaffolds (ENs) have shown promise because they have several advantages. These advantages include matching the anisotropically-aligned geometric structure of tendon extracellular matrix (ECM) and physiologically relevant mechanical properties which may be tuned by controlling the polyblend ratio using both natural and synthetic polymers [3]. For example, a previous report by Yang et al suggested that an aligned fibrous scaffold made by using polycaprolactone (PCL) and methacrylated gelatin (GE) could work well as a tendon graft scaffold [4].…”
Section: Introductionmentioning
confidence: 99%